Early childcare expansion and maternal health - Marina Krauß; Niklas Rott (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
This paper estimates the causal effect of increased availability of early childcare on maternal health. We focus on a substantial expansion of childcare for children under three years in West Germany from 2006 to 2019. By matching county-level childcare attendance rates with individual data from the German Socio-Economic Panel Study (SOEP), we are able to quantify the effects of this expansion on maternal self-assessed health. Using a county-level fixed-effects model, we find that a 10 percentage point increase in the availability of childcare decreases mothers' self-assessed health by 0.173 points on a one to five scale (19% of a standard deviation). A detailed analysis of various health domains reveals negative effects on both physical and mental health as well as on satisfaction with overall health. One plausible mechanism for these negative effects is the transmission of infections from children to mothers. Consistent with this hypothesis, we observe that increased childcare availability leads to mothers worrying more about their children's health. While early childcare expansions offer well-known benefits in many dimensions like maternal employment and child development, our results suggest that there are unintended negative effects in the health domain of mothers.
Keywords: I10; I14; J13; 330; early childcare; maternal health; gender equality